Shale tectonic processes: Field evidence from the Parras Basin (north-eastern Mexico). (December 2020) - Deville, Eric; Dutrannoy, Clement; Schmitz, Julien; Vincent, Benoit; Kohler, Eric; Lahfid, Abdeltif
Abstract: Major decollements located within buried overpressured shale commonly develop in thrust fronts, accretionary prisms and sedimentary deltas controlled by gravity tectonics. In seismic data, it is possible to observe only large scale deformation of what is commonly designed as mobile shale but the precise geometry and the dynamic evolution of these bodies remains poorly understood. It is often difficult to define if we are dealing with ductile or brittle deformation and to understand the role of the fluids in time and space during deformation. For this reason, large scale outcrops were studied in the Parras Basin (Mexico), which makes possible a direct observation of the shale tectonic processes. This work suggests changes in space and time of the deformation processes which occurred within the shale formation hosting the decollement. Distributed deformation was observed within the shale formation hosting the decollement compared to more localized deformation above. Also a change of the rheology of the shale over time occurred progressively toward brittle processes in the whole sedimentary pile. XRD and microscopic studies have shown that diagenetic processes are favored in the shear zones of penetrative deformation leading notably to reverse gradient of illitization. The isotopic analysis of cements in veins and the study of associated fluid inclusions have shown that fluid dynamics also evolved during time showing notably evidence for widespread fluid migration issued from rocks located below the decollement during the beginning of the deformation. Progressively, the tectonic system located above the decollement tends to be preserved from fluid migration coming from below the decollement and to be influenced only by local fluid migration (closed system). Highlights: Outcrops were studied in NE Mexico to understand better the processes of shale tectonics. Shale rocks deformation evolved from ductile toward brittle processes. Fluid migrations occurred from below the decollement during early deformation. The thrust wedge evolved progressively toward a closed hydrodynamic system.